Two vs. one resistance exercise sessions in one day: acute effects on recovery and performance - Bartolomei, S.; Malagoli Lanzoni, I.; Di Michele, R. (Research Quarterly for Exercise and Sport, 2023)
Purpose: The purpose of this study was to compare the recovery response of one resistance training session (1TRS) vs. two resistance training sessions (2TRS) performed in 1 day, on upper body performance, muscle morphology and muscle soreness in trained men. Methods: Twenty-four resistance trained men were randomly assigned into a 1TRS group (N = 12; age = 25.0 ± 2.4 years; body mass = 87.6 ± 14.0 kg; height = 177.1 ± 4.9 cm) or into a 2TRS group (N = 10; age = 24.4 ± 1.6 years; body mass = 81.1 ± 5.6 kg; height = 176.6 ± 6.7 cm). 1TRS performed one training session involving eight sets of 10 reps at 70% of 1RM at the bench press, while 2TRS group divided the same training volume in two workouts, with a recovery time of 4 hr. Performance [bench press throw power (BTP) and isometric bench press (IBP)] and muscle thickness of pectoralis major (PECMT) were assessed at baseline (BL), 15-min, 24-hr and 48-hr post-exercise. Results: Training intensity was significantly higher in 2TRS compared to 1TRS (p < .001). Faster recovery rates were detected for BTP (p = .039) and PECMT (p = .05) in 2TRS compared to 1TRS. Both BTP and PECMT were significantly more affected (p < .05) in 1TRS than in 2TRS at 24 h. Conclusions: Results indicate that the recovery process may be accelerated by splitting a high resistance training volume into two different training sessions performed in 1 day.